Outcomes of Chronic Hepatitis C Therapy in Patients Treated in Community Versus Academic Centres in Canada: Final Results of APPROACH (A Prospective Study of Peginterferon alfa-2a and Ribavirin at Academic and Community Centres in Canada) - Robert P Myers; Curtis Cooper; Morris Sherman; Richard Lalonde; Helga Witt-Sullivan; Magdy Elkashab; Paul Harris; Rob Balshaw; Christopher Usaty; Paul J Marotta (Canadian Journal of Gastroenterology)
BACKGROUND: In patients chronically infected with the hepatitis C virus (HCV), it is not established whether viral outcomes or health-related quality of life (HRQoL) differ between individuals treated at academic or community centres.